Characterizing the Foreshock, Main Shock, and Aftershock Sequences of the Recent Major Earthquakes in Southern Alaska, 2016–2018 - Bukchin, B. G.; Fomochkina, A. S.; Kossobokov, V. G.; Nekrasova, A. K. (Frontiers in Earth Science, 2020)
For each of three major M≥7.0 earthquakes (i.e., the 24 January 2016, M7.1 earthquake 86 km E of Old Iliamna, the 23 January 2018, M7.9 earthquake 280 km SE of Kodiak, and the 30 November 2018, M7.1 earthquake 14km NNW of Anchorage, Alaska) the study considers integral characterization of the foreshock and aftershock sequences in terms of their variations and scaling properties including the behavior of the control parameter η of the unified scaling law for earthquakes (USLE), along with a detailed analysis of the surface wave records for reconstruction of the source in the approximation of the second moments of the stress glut tensor to obtain integral estimates of its length, orientation, and development over time. The three major earthquakes at 600 km around Anchorage are, in fact, very different due to apparent complexity of seismic dynamics in the orogenic corner of the Pacific and North America plate boundary. USLE generalizes the classic Gutenberg-Richter relationship taking into account the self-similar scaling of the empirical distribution of earthquake epicenters. The study confirms the existence of the long-term periods of regional stability of the USLE control parameter that are interrupted by mid- or even short-term bursts of activity associated with major catastrophic events.